2006
DOI: 10.1111/j.1365-2958.2006.05348.x
|View full text |Cite
|
Sign up to set email alerts
|

The tandem GTPase, Der, is essential for the biogenesis of 50S ribosomal subunits in Escherichia coli

Abstract: SummaryA unique GTP-binding protein, Der contains two consecutive GTP-binding domains at the N-terminal region and its homologues are highly conserved in eubacteria but not in archaea and eukaryotes. In the present paper, we demonstrate that Der is one of the essential GTPases in Escherichia coli and that the growth rate correlates with the amount of Der in the cell. Interestingly, both GTP-binding domains are required at low temperature for cell growth, while at high temperature either one of the two domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
135
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(148 citation statements)
references
References 41 publications
12
135
1
Order By: Relevance
“…Based on these and additional data, the authors propose that the final stages of ribosome maturation take place in conjunction with its first round of initiation. This model can rationalize several earlier observations, including the presence of precursor rRNAs in polysomes (36,37), links between IF2 and ribosome assembly (12,38), and inhibition of 16S rRNA processing resulting from defects in 50S assembly (39,40).…”
Section: Discussionmentioning
confidence: 50%
“…Based on these and additional data, the authors propose that the final stages of ribosome maturation take place in conjunction with its first round of initiation. This model can rationalize several earlier observations, including the presence of precursor rRNAs in polysomes (36,37), links between IF2 and ribosome assembly (12,38), and inhibition of 16S rRNA processing resulting from defects in 50S assembly (39,40).…”
Section: Discussionmentioning
confidence: 50%
“…[4][5][6] Even though there is low primary sequence similarity among different GTPase families, most GTPases have an impressively common structural topology consisting of six b-strands surrounded by five a-helices. 4,5,7 Previously we characterized an essential GTPase, Der (double Eralike protein), from Escherichia coli (EcDer) [8][9][10][11][12] and from a hyperthermophilic bacterium Thermotoga maritima (TmDer). 8,13 The 3D structure of TmDer was solved by X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In case of T. maritima Der, each of the two Der GTP-binding domains expressed separately has an intrinsic GTPase activity, though the activity of the N-terminal GD1 domain is stronger than that of the GD2 domain. 13 It has been demonstrated that Der has a critical role in 50S subunit biogenesis, as it associates with 50S subunit in the presence of a GTP analog 9,15 and its depletion caused conformational instability of 50S subunit at a low Mg 2+ concentration. 9 GTP binds to Der in a cooperative manner and the interruption of cooperative nucleotide association disrupts the interaction of Der with the 50S subunit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations